Risk Factors Associated with Preterm Delivery After Open Fetal Myelomeningocele Repair [30N]. (May 2017) - Said, Heather M.; Vricella, Laura K.; Miller, Collin; Elbabaa, Samer; Vlastos, Emanuel
Abstract : INTRODUCTION: Although open fetal myelomeningocele (MMC) repair increases the risk of preterm delivery (PTD), specific risk factors for this outcome have not been identified. The objective of this study is to determine whether gestational age at the time of open fetal MMC repair is a risk factor for PTD. METHODS: A retrospective cohort of 51 consecutive open fetal MMC repairs between 2011-2016 was analyzed by gestational age at time of surgery. Primary outcome was delivery <37w0d. Secondary outcomes were PPROM, delivery < 34w0d, latency from MMC repair to delivery and neonatal outcomes. RESULTS: Groups were similar in demographic and intraoperative factors. On univariate analysis, delivery <37w0d was more frequent with earlier MMC repair (94% < 24w0d, 69% 24w0d-24w6d and 57% >25w0d, p=0.031), whereas delivery < 34w0d was not (41% < 24w0d, 23% 24w0d-24w6d and 19% >25w0d, p=0.317). Survival-curve pairwise comparisons demonstrated a difference between the < 24w0d and > 25w0d groups (p=0.027). PPROM was more frequent with earlier MMC repair (71% < 24w0d, 31% 24w0d-24w6d and 30% >25w0d, p=0.041). Mean latency from MMC repair to delivery was similar among groups (73 days for < 24w0d, 73 days for 24w0d-24w6d and 67 days for >25w0d, p=0.727), as were neonatal outcomes. On multivariate analysis, earlier gestational age at MMC repair was associated with delivery before 34 weeks (p=0.039; RR 2.13; 95% CI 1.04-4.36) and 37 weeks (p=0.016; RR 3.47; 95% CI 1.26-9.59). CONCLUSION: Earlier gestational age at open fetal MMC repair was associated with preterm delivery before 37 and 34 weeks and PPROM.